Weathering the Storm : Independent Writing Programs in the Age of Fiscal Austerity. - Matzen Jr., Richard N. (Utah State University Press, 2019)
"Assesses the socio-economic and political conditions that surrounded the rise of independent writing programs since the 2008 financial collapse. Looking at institutional conditions and challenges programs have faced in the last ten years as they struggled to stake their turf in a rapidly changing educational environment"--Provided by publisher.